Harmonizing plasmonic and photonic effects to boost photocatalytic H2 production over 550 mmol⋅h-1⋅gcat-1 - Raja Mogan, Tharishinny (2024)
Integrating plasmonic nanoparticles with photonic crystals holds immense potential to enhance green hydrogen photosynthesis by amplifying localized electromagnetic field through generating surface plasmons and slow photons. Current plasmonic photonic designs primarily employ semiconductor-based structural backbone deposited with plasmonic nanoparticles. However, the competition between various optical phenomena in these ensembles hinders effective field enhancement rather than facilitating it. This limitation creates a formidable performance bottleneck that retards hydrogen evolution. Herein, we enhance plasmonic catalysis for efficient hydrogen evolution by effectively harmonizing plasmonic and photonic effects. This is achieved by using inert SiO2 opal as a non-photoabsorbing photonic framework. By aligning the excitation wavelengths of surface plasmons and slow photons, our optimized plasmonic photonic crystals demonstrates a remarkable H2 evolution rate of 560 mmol h-1  gAg -1 , surpassing bare plasmonic Ag nanoparticles by >106 -fold and other high-performance photocatalytic designs by 280-fold. Mechanistic studies highlight the pivotal role of the non-photoabsorbing photonic backbone in facilitating effective light confinement through the photonic effect. This in turn boosts the plasmonic field for enhanced photocatalytic H2 evolution, even without needing additional co-catalysts. Our work offers valuable insights for future design of electromagnetically hot plasmonic catalysts to achieve efficient light-to-chemical transformations in diverse energy, chemical, and environmental applications.